MENINGKATKAN KEMAMPUAN LITERASI DENGAN PENDEKATAN TEORI VYGOTSKY ANAK SEKOLAH DASAR - Dian Aditya Suryani; Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the literacy skills of elementary school students through the application of Vygotsky's theory, which emphasizes the importance of social interaction, gradual assistance, and collaborative activities in the learning process. The background of this study stems from initial findings that the literacy skills of students at MI Ma'arif 02 Bajing Kulon are still low, as evidenced by their difficulty in understanding reading content, determining main ideas, and composing coherent writing. To address these issues, this study used a classroom action research method with two cycles, which included the stages of planning, implementation, observation, and reflection. In each cycle, teachers applied small group-based learning strategies, provided gradual guidance, used trigger questions, and conducted collaborative reading and writing activities so that students could receive support according to their ability levels. The results of the study indicate that Vygotsky's theory approach has a significant positive impact on improving students' literacy skills. Before the intervention, the average literacy score of students was 62.4 with a completion rate of 32%. After the intervention in cycle I, the average score increased to 71.5 with a completion rate of 60%. In cycle II, the average score increased again to 81.2 with a mastery level of 88%. In addition to the increase in scores, observations also noted more positive changes in learning behavior, such as students' courage in reading, improved discussion skills, and independence in writing summaries. These findings confirm that support provided through social interaction and gradual guidance can help students move from their actual abilities to their potential abilities. Thus, Vygotsky's theory approach has proven effective in improving literacy skills while encouraging social development and self-confidence in elementary school students.